Shadow cast of noncommutative black holes in Rastall gravity - Övgün, Ali; Sakalli, Izzet; Saavedra, Joel; Leiva, Carlos (World Scientific Publ Co Pte Ltd, 2020)
We study the shadow and energy emission rate of a spherically symmetric noncommutative black hole in Rastall gravity. Depending on the model parameters, the noncommutative black hole can reduce to the Schwarzschild black hole. Since the nonvanishing noncommutative parameter affects the formation of event horizon, the visibility of the resulting shadow depends on the noncommutative parameter in Rastall gravity. The obtained sectional shadows respect the unstable circular orbit condition, which is crucial for physical validity of the black hole image model.
Keywords: Black hole shadow; noncommutative black hole; Rastall gravity; energy emission rate